PERBANDINGAN KEMAMPUAN MENULIS KARANGAN NARASI MENGGUNAKAN TEKNIK REKA CERITA GAMBAR DENGAN TEKNIK PARAFRASE PUISI SISWA KELAS X SMA NEGERI 3 KOTA BENGKULU - Heny Friantary (At-Ta'lim : Media Informasi Pendidikan Islam, 2017)
This study aims to see the description of the following. First, the ability to write a narrative essay using the technique of making pictures of class X students of SMA Negeri 3 Kota Bengkulu. Second, the ability to write narrative essay using poetry paraphrase technique of grade X SMA Negeri 3 Bengkulu. Third, the comparative ability to write narrative essay using the technique of picture storytelling with poetry paraphrasing technique of class X students of SMA Negeri 3 Kota Bengkulu. The subjects of this study were the students of grade X SMA Negeri 3 Kota Bengkulu which amounted to 30 people. The type of research used is quantitative research with descriptive method. This research data is obtained through narrative writing test using image-making techniques and narrative writing test using poetry paraphrase technique. The test of narrative writing ability is used to know the comparative ability to write narrative essay using the technique of picture storytelling with poetry paraphrasing technique of grade X students of SMA Negeri 3 Kota Bengkulu with data analysis technique done descriptively. Based on the results of the study, the following conclusions are obtained. First, the ability to write a narrative essay using the technique of making pictures of class X students of SMA Negeri 3 Kota Bengkulu is generally quite good (76.67). Second, the ability to write a narrative essay using poetry paraphrase technique of grade X SMA Negeri 3 Bengkulu is generally more than enough (69,5).